Investigations and assessment of the dust hazard state after the coal dust explosions on 2002 in the ‘Jas-mos’ and in the ‘Rudul/towy’ collieries - K. Cybulski (The Southern African Institute of Mining and Metallurgy, 2003)
In 2002 a coal dust explosions occurred in the Polish collieries “Jas-Mos” and “Rydultowy” in the Upper Silesia coal basin. In the “Jas-Mos” colliery the coal dust explosion was initiated in the face of gallery by explosives and causing ten death. The stone dust barrier extinguished the flame, stopped the explosion development and saved forty nine miners working in that area. In the “Rydultowy” colliery methane inflammation caused three deaths and seven serious burns and ignited the coal dust explosion. The coal dust explosion was stopped by stone dust barrier and did not cause any victims itself. This paper presents the investigation carried out by the Central Mining Institute Experimental Mine “Barbara” and shows that the stone dust barriers remain still a basic mean for suppression of coal dust explosion in mines. The investigation were aimed at determining the cause of explosion and circumstances that led to their propagation. The evaluation of the state of dust explosion hazard in the areas of accidents have been performed, and the range of flame estimated.